Minireview of potential applications of hydrochar derived from hydrothermal carbonization of biomass - Fang, June; Zhan, Lu; Ok, Yong Sik; Gao, Bin (Journal of industrial and engineering chemistry (Seoul, Korea), 2018)
[Display omitted] This review provides a brief overview of the potential applications of hydrochar and its derivatives. It first summarized the key processes of hydrothermal carbonization (HTC) of biomass and basic properties of the resulting hydrochar. Most of the efforts of this review is then on reviewing the potential applications of hydrochar in various fields including environment, energy, adsorbent and medical applications. It also discusses different modification and activation methods to produce hydrochar-based engineered carbon materials for enhanced performances in those applications, particularly with respect to their application as low-cost adsorbents for the removal of heavy metals, organics, phosphate and pathogens.